The therapeutic effects of physical treatment for patients with hereditary spastic paraplegia: a narrative review - Di Ludovico, Armando; Ciarelli, Francesca; La Bella, Saverio; Scorrano, Giovanna; Chiarelli, Francesco; Farello, Giovanni (Frontiers in Neurology, 2023)
Background Hereditary spastic paraplegia (HSP) encompass a variety of neurodegenerative disorders that are characterized by progressive deterioration of walking ability and a high risk for long-term disability. The management of problems associated with HSP, such as stiffness, deformity, muscle contractures, and cramping, requires strict adherence to recommended physiotherapy activity regimes. The aim of this paper is to conduct a critical narrative review of the available evidence focusing exclusively to the therapeutic advantages associated with various forms of physical therapy (PT) in the context of HSP, emphasizing the specific benefit of every distinct approach in relation to muscle relaxation, muscle strength, spasticity reduction, improvement of weakness, enhancement of balance, posture, walking ability, and overall quality of life. Methods To conduct a literature review, the databases PubMed, Scopus, and DOAJ (last access in June 2023) were searched. Results The PubMed search returned a total of 230 articles, Scopus returned 218, and DOAJ returned no results. After screening, the final list included 7 papers on PT treatment for HSP patients. Conclusion Electrostimulation, magnetotherapy, hydrotherapy, PT, robot-assisted gait training, and balance rehabilitation have the potential to increase lower extremity strength and decrease spasticity in HSP patients.